2023
DOI: 10.1177/17470218231172908
|View full text |Cite
|
Sign up to set email alerts
|

Syntactic adaptation leads to updated knowledge for local structural frequencies

Abstract: Syntactic adaptation has been shown to occur for various temporarily ambiguous structures wherein an initially unexpected resolution becomes easier to process after repeated exposure. More controversial and less replicated is the claim that this adaptation toward a locally frequent structure occurs due to a strategic shifting of expectations to match short-term statistical regularities such that readers adapt away from the a priori more frequent structure. Experiment 1 replicates the initial adaptation toward … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 72 publications
(125 reference statements)
0
0
0
Order By: Relevance
“…Additional recent work has replicated the original finding with reduced relative clauses (Dempsey et al 2020(Dempsey et al , 2023Yan and Jaeger 2020) as well as expanded the range of structures involved in successful adaptation to include relative clause attachment ambiguities (Chun 2018;Kamide 2012), subject versus object relative clauses (Wells et al 2009), and coordination (Kaan et al 2019) and dialectal differences (Boland et al 2023;Fraundorf and Jaeger 2016;Kaschak and Glenberg 2004).…”
Section: The Current Studiesmentioning
confidence: 77%
“…Additional recent work has replicated the original finding with reduced relative clauses (Dempsey et al 2020(Dempsey et al , 2023Yan and Jaeger 2020) as well as expanded the range of structures involved in successful adaptation to include relative clause attachment ambiguities (Chun 2018;Kamide 2012), subject versus object relative clauses (Wells et al 2009), and coordination (Kaan et al 2019) and dialectal differences (Boland et al 2023;Fraundorf and Jaeger 2016;Kaschak and Glenberg 2004).…”
Section: The Current Studiesmentioning
confidence: 77%
“…is referred to as the "garden-path effect". Several self-paced reading studies have reported a reduction in the garden-path effect as more sentences of the target structure are read (e.g., Atkinson 2016;Dempsey et al 2023;Fine et al 2010Fine et al , 2013Kaan et al 2019). It is tempting to interpret an increasingly smaller garden-path effect as evidence that readers start expecting the initially less-preferred structure.…”
Section: Introductionmentioning
confidence: 99%
“…This preference reversal effect is convincing evidence that adaptation has taken place. However, many studies fail to find such reversal effects (c.f., e.g., Atkinson 2016;Dempsey et al 2020Dempsey et al , 2023Harrington Stack et al 2018). Power analyses (Prasad and Linzen 2021) suggest that the lack of consistency among studies may be due to a lack of power, and that more than 1200 participants are needed to detect adaptation in most between-group studies using self-paced reading.…”
Section: Introductionmentioning
confidence: 99%